2015
DOI: 10.1080/17415993.2015.1025404
|View full text |Cite
|
Sign up to set email alerts
|

Fast and efficient green synthesis of thiosulfonate S-esters by microwave-supported permanganate oxidation of symmetrical disulfides

Abstract: Potassium permanganate absorbed on copper(II) sulfate pentahydrate has been found to be an efficient, inexpensive, and green oxidation agent for the synthesis of "symmetrical" thiosulfonate S-esters by oxidation of the corresponding symmetrical disulfides. The oxidation reactions were carried out under solvent-free reaction conditions within 15 min under the influence of microwave irradiation, as well as (for comparison) supported by conventional heating, to afford yields of the thiosulfonate S-esters in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 68 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…The thiosulfonate S-esters 1-5 were synthesized by microwavesupported permanganate oxidation of the corresponding symmetric disulfides [4]. It should be noted, that S-methyl methanethiosulfonate (1) and S-phenyl benzenethiosulfonate (5) are also commercially available (Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thiosulfonate S-esters 1-5 were synthesized by microwavesupported permanganate oxidation of the corresponding symmetric disulfides [4]. It should be noted, that S-methyl methanethiosulfonate (1) and S-phenyl benzenethiosulfonate (5) are also commercially available (Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Since thiosulfonate S-esters are commercially available only to a very limited extent, the synthetic accessibility of these compounds, in particular via modern environmentally friendly methods, is still of importance [4]. In connection with our recent preparation of ''symmetric'' thiosulfonate S-esters (R 1 ASO 2 ASAR 2 , R 1 =R 2 ) by microwave supported permanganate oxidation of the corresponding symmetric disulfides (R 1 ASASAR 2 , R 1 =R 2 ) [4], the products were characterized by spectroscopic methods, including IR spectroscopy. However, a comprehensive search for comparative background information on IR data for thiosulfonate S-esters resulted in surprisingly few hits [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, another study reported the synthesis of thiosulfonates from disulfides by oxidation using oxone in combination with the alkali‐metal chlorides and bromides . In the meantime, Duus and co‐workers described an efficient po‐tassium permanganate and copper sulfate promoted synthetic method for the preparation of thiosulfonates in fair to high yields by solvent‐free oxidation of symmetrical disulfides under the assistance of microwave irradiation or conventional heating . Recently, the decomposition of sulfonyl hydrazides has been reported for the preparation of thiosulfonates in fair to high yields .…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the lowest reaction PMI value of all direct oxidation methodologies was obtained. Alternatively, potassium permanganate absorbed on copper(II) sulfate pentahydrate was proposed by the group of Luu as a green promoter for the oxidation of aliphatic disulfides ( 3 ) (route 14) . The reactions were carried out either under microwave irradiation or by conventional heating in the absence of solvent.…”
Section: Thiosulfonate Synthesismentioning
confidence: 99%